Influence of parental involvement and students' emotional intelligence on the academic achievement of first-year students in Nigerian universities (2018)
The current state of education in Nigeria as evidenced by student’s performance at the undergraduate level examinations has been worrisome. The low performance has generated much concern for stakeholders in education. Varied problems might be responsible for this poor performance which includes parental involvement and emotional intelligence. This study investigated parental involvement and students’ emotional intelligence on academic achievement among undergraduate students in Nigerian Universities. The study is a survey research using multistage sampling technique. Three instruments- Parental Involvement Rating Scale (r= 0.75), Students’ Emotional Intelligence Scale (r=0.73) and General Study Achievement Test (r=0.69) were used for data collection. Data collected from 500 respondents selected proportionate to size from three universities owned by federal, state and private owners was analysed using frequency counts, percentages, Pearson product moment correlation and multiple regression at p<0.05 significance level. Results show that 358(71%) respondents claimed that they helped their children make good grades in school. More students 383(78%) reportedly agreed that they understood their emotion. The highest relationship was between social awareness and academic achievement. (r= 0.188). Among the predictor variables, self-awareness was the most potent and contributed most to the model (that parental involvement and students’; emotional intelligence should he improved in the university system.: Town and gown should be encouraged in ensuring that parents' are f involved in: university collaboration. Lecturers should monitor and understand their students’ emotional intelligence in the process of teaching and learning. = 0.324); followed by social awareness (β = 0.13,6); and then academic support (β = 0.115). There existed a linear relationship between the predictor variables and the criterion variable. Seven predictor variables accounted for 13.6% (Adjusted R2= 0.136) of the variance in students’ academic achievement. It was recommended that parental involvement and students’; emotional intelligence should he improved in the university system. Town and gown should be encouraged in ensuring that parents' are involved in: university collaboration. Lecturers should monitor and understand their students’ emotional intelligence in the process of teaching and learning.